2012
DOI: 10.1016/j.forsciint.2012.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-platform comparison of ten commercial master mixes for probe-based real-time polymerase chain reaction detection of bioterrorism threat agents for surge preparedness

Abstract: -platform comparison of ten commercial master mixes for probe-based real-time polymerase chain reaction detection of bioterrorism threat agents for surge preparedness" (2012). US Army Research. 188.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 18 publications
0
21
1
1
Order By: Relevance
“…Increase of commercial master mix kits enabled diagnostic laboratories to implement real-time PCR. It has been demonstrated that the reverse transcription reaction mainly depends on the initial molecular step (the reverse transcription), choice of master mix reagents, quality of enzymes, concentration of reaction mix components, such as primers, probes and methodology used that can impact the sensitivity of results for real-time PCR assays (SERGERIE et al, 2007;BUZARD et al, Ciência Rural, v.46, n.9, set, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Increase of commercial master mix kits enabled diagnostic laboratories to implement real-time PCR. It has been demonstrated that the reverse transcription reaction mainly depends on the initial molecular step (the reverse transcription), choice of master mix reagents, quality of enzymes, concentration of reaction mix components, such as primers, probes and methodology used that can impact the sensitivity of results for real-time PCR assays (SERGERIE et al, 2007;BUZARD et al, Ciência Rural, v.46, n.9, set, 2016.…”
Section: Resultsmentioning
confidence: 99%
“…A alternação de uso de equipamentos, de maneira semelhante, pode trazer oscilações nos resultados de Ct obtidos, sobretudo quando não houver padronização de calibração dos aparelhos (Sivaganensan et al 2012). Buzard et al (2012) sinalizaram que há limitações em estudos comparativos de técni-cas com alternância de equipamentos e reagentes, uma vez que nem sempre é possível seguir todas as recomendações de ambos os fabricantes. Por este motivo, técnicas de qPCR, para fins diagnósticos, precisam ser avaliadas sob méto-dos estatísticos em que se observem tanto a repetitividade quanto a reprodutibilidade, isto é, a correspondência dos resultados de uma mesma amostra em diferentes rodadas (Albano & Raya-Rodriguez, 2009).…”
Section: Quadro 5 Valores De Ct Obtidos Nas Três Qpcr Para Psa Em Teunclassified
“…Ebola infection can be confirmed through several types of laboratory tests: ELISA, Real Time RT-PCR, antigen detection tests or serum neutralization test [4] executed only in laboratories provided with specific equipments [3]. Filoviruses are classified as Biological Level 4 (BSL4) agents by Health and Safety Executive [15] and as category A biological warfare agents (BWA) by the Centers for Disease Control and Prevention [16]. The nature of the virus make it suitable as BWA for the high lethality in human infection and for the potential oral and conjunctival viral transmission demonstrated with aerosolized virus suspensions in non-human primates [17].…”
Section: Introductionmentioning
confidence: 99%